Layered MXene Protected Lithium Metal Anode as an Efficient Polysulfide Blocker for Lithium‐Sulfur Batteries. Issue 9 (19th May 2020) - Li, Wantang; Zhang, Yifang; Li, Huan; Chen, Zijin; Shang, Tongxin; Wu, Zhitan; Zhang, Chen; Li, Jia; Lv, Wei; Tao, Ying; Yang, Quan‐Hong
Abstract: The shuttle effect of lithium polysulfides (LiPSs) from sulfur cathode to lithium (Li) anode is one of the main obstacles for lithium‐sulfur (Li−S) batteries. The severe corrosion of Li metal anode by the dissolved LiPSs bottlenecks the efficient operation of Li−S batteries, however, the anode part has not been received much attention compared to those extensive efforts related to the cathode designs. Herein, we show that the interface between Ti3 C2 T x (T=−OH, −F)‐based MXene and reduced graphene oxide (rGO) is able to guide uniform Li nucleation, promoting highly reversible and dendrite‐free Li plating/stripping. Such the Li anode demonstrates excellent cycling stability for more than 1000 hours even under ultra‐high rate (10 mA cm −2 ) and high areal capacity (3 mAh cm −2 ). More importantly, the well‐designed 2D layered structure by coupling the Ti3 C2 T x with a graphene scaffold, is highly efficient to block the shuttled polysulfides and inhibit the corrosion of the lithium metal anode. As a result, the Li−S full battery exhibits a stable cycling stability with a high Coulombic efficiency of 99.8 % over 300 cycles. This work suggests the design strategy of Li metal anode especially targeting at the sulfur cathode, and we hope it can provide valuable inspirations for the future design of Li metal anodes for more practical Li−S batteries. Abstract : MXene shield : The rGO/Ti3 C2 T x interfaces favor Li nucleation and deposition, contributing to dendrite‐free Li plating/stripping behaviors inside the scaffold. The membrane also mitigates the side reactions of Li by blocking the shuttled lithium polysulfides, which promotes the efficient cycling of Li−S batteries.